DETERMINANTS OF TEACHERS’ PSYCHOLOGICAL ABUSE AMONG SECONDARY SCHOOL STUDENTS IN NIGERIA - Gesinde, Abiodun .M.; Sanu, Oluwafunto .J. (European Scientific Journal, ESJ, 2013)
﻿Teachers are employed in schools to perform specific roles that will support students’ crave for academic excellence. For students to realize this, the academic environment must be devoid of psychological disturbances and intimidation. Disappointedly, studies have shown that emotional abuse existed in schools and perpetrators included teachers. Researches in this area have shown variables such as parental education, family type and size, socio-economic status as correlates of teachers’ psychological abuse. Apart from the fact that some predicting variables are yet to be tested via researches, the joint and separate effects of some variables are yet to be empirically determined. Therefore, the current study examines the extent to which the separate and combination of gender, age, class and school type of students would impact on teachers’ psychological abuse. The sample for the study consists of 500 students randomly selected from ten secondary schools in Ado-Odo Ota Local Government Area of Ogun State, Nigeria. ‘Teachers’ Psychological Abuse Rating Scale’’ with a 4-point rating scale is employed to generate data. The results of the two hypotheses analyzed with stepwise multiple regression analysis show that the combination of gender, age class, and school type could only account for 16.2% of the variance in teachers’ psychological abuse with the class of the participants (junior and secondary schools) as the most potent predictor. It is recommended that multi-dimensional research efforts should be adopted to isolate all contributing variables of psychological abuse by teachers and psychologists should cooperatively develop psycho-educational interventions on relational skills development.